2015
DOI: 10.1097/md.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Version, Neck-Shaft Angle, and Acetabular Anteversion in Chinese Han Population

Abstract: Anatomic data regarding femoral version, neck-shaft angle, and acetabular anteversion are still limited in Chinese Han adult population. The aim of this study was to investigate the effects of age, sex, and body laterality on the 3 important anatomic indicators in Chinese Han healthy adults.Measurements were performed independently by 3 experienced observers using the picture archiving and communication system (PACS) in healthy adults who had received imaging tests of the femur and acetabulum between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 36 publications
8
23
0
Order By: Relevance
“…Overall, the patients in the CFP group experienced seven intraoperative fractures of the lateral femoral diaphysis at the tip of the stem and six of these involved an exaggerated neck-shaft angle. The CFP prosthesis is designed in accordance with the normal anatomy of the femur, with two neck-shaft angles (126° and 117°); Jiang et al [ 19 ] reported that the mean neck-shaft angle in a Chinese Han population was 133°. They also showed that adults younger than 60 years had a significantly higher neck-shaft angle.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the patients in the CFP group experienced seven intraoperative fractures of the lateral femoral diaphysis at the tip of the stem and six of these involved an exaggerated neck-shaft angle. The CFP prosthesis is designed in accordance with the normal anatomy of the femur, with two neck-shaft angles (126° and 117°); Jiang et al [ 19 ] reported that the mean neck-shaft angle in a Chinese Han population was 133°. They also showed that adults younger than 60 years had a significantly higher neck-shaft angle.…”
Section: Discussionmentioning
confidence: 99%
“…Current prosthesis selection in Chinese clinical practice is based on the results of foreign studies, such as the Nobel index of femoral medullary morphology. [ 16 ] Many other studies have focused on the morphology of hips in Caucasians, but corresponding studies in Asian populations are limited, particularly data on proximal femoral geometric parameters in Han Chinese. [ 16 ] Our study analyzed the geometric parameters of the hip in 198 patients with hip fractures compared to different types of hip fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Many other studies have focused on the morphology of hips in Caucasians, but corresponding studies in Asian populations are limited, particularly data on proximal femoral geometric parameters in Han Chinese. [ 16 ] Our study analyzed the geometric parameters of the hip in 198 patients with hip fractures compared to different types of hip fractures. Our goal was to provide evidence and guidance for selection and manufacture of clinical prostheses, as well as providing evidence for the accurate reconstruction of proximal femurs in Chinese hip fracture patients.…”
Section: Introductionmentioning
confidence: 99%
“…(Malaysian -19.96°, Japanese -20.2°, Indian -19°, Chinese -18.79°) (5)(6)(7)(8). The average CE (38.3 ± 6.4°) was greater than mean the of Chinese population (33.3° in male and 32.8° in female) (8) and Japanese population (35.8°) (6). The CE had a significant positive correlation with AI and AA.…”
Section: Discussionmentioning
confidence: 87%